FROM IMPLEMENTATION TO DISSEMINATION OF KANGAROO CARE IN SANTA CATARINA: A FOUCAULT'S ANALYSIS. - dos Passos Aires, Luana Cláudia; Wilhelm, Laís Antunes; de Lima, Margarete Maria; Boscoli de Oliveira Alves, Isadora Ferrante; Delgado, Bruna Schiphorst; Costa, Roberta (Texto & Contexto Enfermagem, 2023)
Objective: to know the process of kangaroo care implementation and dissemination in the state of Santa Catarina. Method: this is socio-historical research with a qualitative approach, with data collection carried out from January to November 2019, through interviews with 12 oral sources. Analysis was carried out in the light of genealogical analysis proposed by Foucault, with the help of Atlas.ti Cloud®. Results: the process of kangaroo care implementation and dissemination in Santa Catarina happened from the breaking of resistance to the light of scientific knowledge, training and awareness that gradually captivated health professionals for the incorporation of new knowledge in neonatal care practice. Conclusion: kangaroo care implementation as a public health policy configured a paradigm shift in neonatal care in Santa Catarina. Although scientifically supported, it took years to materialize in the state and still faces resistance.